PEREMPUAN MINANGKABAU DALAM SENI LUKIS - Drs. Erfahmi, M.Sn., Harmukhlis, Drs. Abd. Hafiz, M.Pd., (Serupa The Journal of Art Education, 2018)
The purpose of the creation of this work is to present a painting by visualizing the influence of modernization on the life of Minangkabau women into paintings with decorative patterns. For the method of creation of art, the writer uses five stages: preparation stage, elaboration stage, synthesis stage, realization stage of concept and completion stage and last author held exhibition of work. The ten works that the authors present represent the theme that the author lifted, containing about the problems associated with Minangkabau women in the era of modernization, contains about the phenomena that occur around the life of the author. The tenth works include: 1) Alaik Usai Anak Kalua, 2) Tempting, 3) Shame, 4) Forgotten, 5) Ethics, 6) Show, 7) Western Culture, 8) Dance Plates, 9) Forgot self, and 10) Adaik Basandi Parampuan.Kata Kunci: Perempuan Minangkabau, Seni Lukis, Dekoratif.